SS Beams with an End Couple:
∑ Fy = 0 so that RA + RB = 0
Taking moments around A,
RB × l = M 0
∴ RB = + M0 / l (↑)
![845_SS Beams with an End Couple.png](https://www.expertsmind.com/CMSImages/845_SS%20Beams%20with%20an%20End%20Couple.png)
Figure: SS Beam with End Couple
From Equation. (66) & (67),
R A =- M 0 / l (↓)
Let a section X-X at a distance from x from A,
M = R A . x = - (M 0 / l ) x
The governing equation for deflection is :
![2404_SS Beams with an End Couple1.png](https://www.expertsmind.com/CMSImages/2404_SS%20Beams%20with%20an%20End%20Couple1.png)
EI (d y/dx) = (M0/2l )x2 +C1
Integrating the Eq. (69), we will get
EI dy /dx=- (M 0/2l ) x2 + C1
EIy =- M 0 /6l x3 + C1 x + C2
The constants C1 and C2 may be found from the boundary conditions. The boundary conditions are following:
at A, x = 0, y = 0 --------- (1)
at B, x = 0, y = 0 ----------- (2)
By applying the boundary condition (1) into the Eq. (71), C2 = 0.
By applying the BC (2) into the Equation (71),
0 =- M 0 l2 /6 + C l l ∴ C1 = M 0 l/6
The slope & deflection equation shall be :
EI dy/ dx =- M 0 x2 /2 l + M 0 l /6
EIy =- M 0 /6 l x3 + M0lx/6
Slope at A, (x = 0)
θ A = + M 0 l/6EI
Slope at B, (x = l)
EI θ B = - M 0 l/2 + M 0 l /6= - M 0 l/3
∴ θB = - M 0 l / 3 EI
Slope at C, (x = l /2),
EI θ C = - M 0 ( l/2) 2+ M 0 l /6 = - M 0 l/8 + M 0 l/6
∴ θC = + M 0 l /24 EI
Deflection at C, ( x = l /2) ,
EIy =- M 0 /6l( l /2)3 + (M 0 l/6) ( l /2)
=- M0 l 2 /48 + M0 l 2/12 = M 0 l 2 / 16
∴ yC =+ M0 l 2/16 EI
![1277_SS Beams with an End Couple2.png](https://www.expertsmind.com/CMSImages/1277_SS%20Beams%20with%20an%20End%20Couple2.png)
Figure